Palynostratigraphic study (dinoflagellate cysts) of the Callovian–Oxfordian in Essaouira-Agadir Basin, Morocco - Soukaina Jaydawi; Touria Hssaida; Abdelkrim Afenzar; Hicham Si Mhamdi; Sara Chakir; Khaoula Chafai; Hanane Khaffou (Swiss Journal of Palaeontology)
Abstract Numerous geological studies have focused on the sedimentary basins of the Moroccan Atlantic margin, driven by their potential hydrocarbon and the abundance of well-exposed and rich fossiliferous outcrops. This study is a contribution to palynostratigraphic study of the Essaouira-Agadir Basin. Here we revise previous dating efforts and establish a scale based on dinoflagellate cysts for the Tethyan and Atlantic realms, which would be correlatable with the one established for the entire NW European (subboreal realm). This work presents the preliminary results of the 75-m-thick Iggi N’Tarhzout section, located north of Agadir city, in the Imouzzer Ida Outanane mountain range. The collected samples revealed rich, diverse, and well-preserved dinoflagellate cyst associations, with the occurrence of high-resolution stratigraphic markers. Thus, the upper Callovian is identified at the base of this section by the presence of: Ctenidodinium ornatum, Dichadogonyaulax sellwoodii, Endoscrinium? centriconnata, Systematophora areolata, and Wanaea thysanota. The upper part of the section is attributed to the Upper Oxfordian due to the association composed of: Systematophora penicillata, Endoscrinium galeritum, Systematophora daveyii, Ctenidodinium ornatum and Cribroperidinium granuligerum.